The effect of lowering cholesterol through diet on serum prostate-specific antigen levels: A secondary analysis of clinical trials - Jayalath , Viranda H.; Lajkosz , Katherine; Fleshner , Neil E.; Hamilton, Robert J.; Jenkins , David J.A. (Canadian Urological Association Journal, 2022)
Importance: Statins appear to lower serum prostate-specific antigen (PSA) and improve prostate cancer (PCa) outcomes through cholesterol-dependent and independent mechanisms. While dietary modifications have an established role in serum cholesterol reduction, whether diet-driven cholesterol reductions yield similar PCa benefits to that observed with statins is unclear. We aimed to study the effect of diet-driven cholesterol reduction on serum PSA and estimated-PCa risk. Methods: A total of 291 men from six published randomized controlled trials of dietary interventions were included. Men were aged ≥40 years, free of PCa, and had baseline PSA <10.0 ng/mL. Participants received one of four diets (high-fiber, low-glycemic index, low-glycemic load, or cholesterol-lowering) for 8–24 weeks. The primary outcome evaluated the association between change from baseline low-density lipoprotein cholesterol (LDL-C) and PSA. How cholesterol reduction modified PCa risk was estimated using the Prostate Cancer Prevention Trial (PCPT) risk calculator (limited to age ≥55 years, baseline PSA ≥1.0 ng/mL). Results: Baseline PSA was 0.90 ng/mL (interquartile range [IQR] 0.55–1.60) and LDL-C was 90 mg/dL (IQR 69–125). In multivariate regression, PSA decreased 1.9% (95% confidence interval [CI] 0.55–3.2, p=0.005) per 10% reduction in LDL-C. This regression was greater in men with baseline PSA ≥2.0 ng/mL (-5.4%, 95% CI 2.2–8.6] per 10% LDL-C reduction, p-interaction=0.001). In men with estimable PCPT risk, statin-comparable LDL-C reductions (≥15%) reduced PSA by 12% (p<0.001) and estimated PCa risk by 6.5% (p=0.005). Conclusions: This is the first study to show that serum cholesterol reduction through dietary interventions significantly lowered serum PSA and estimated PCa risk. Whether cholesterol-lowering diets improve PCa outcomes warrants investigation.